Intake of thickened liquids by hospitalized adults with dysphagia after stroke. (October 2014) - Murray, Jo; Miller, Michelle; Doeltgen, Sebastian; Scholten, Ingrid
Abstract There is widespread concern that individuals with dysphagia as a result of stroke do not drink enough fluids when they are prescribed thickened liquids. This paper details a retrospective audit of thickened liquid consumption of 69 individuals with dysphagia following stroke in acute and rehabilitation hospitals in Adelaide, South Australia. Hospitalized individuals with dysphagia following stroke drank a mean of 781 ml (SD = 507 ml) of prescribed thickened liquids per day, significantly less in the acute setting (M = 519 ml, SD = 305 ml) than in the rehabilitation setting (M = 1274 ml, SD = 442 ml) (t(67) = −8.34, p < .001). This daily intake of thickened liquids was lower than recommended standards of fluid intake for hospitalized adults. Fluid intake could be increased with definitive protocols for the provision and monitoring of consumption of thickened liquids, by offering more fluid via food or free water protocols or by routine use of non-oral supplementary routes. Future research into the effectiveness of such recommendations needs to evaluate not only the impact on fluid intake but also on health outcomes.